BODY IMAGE AND SELF-ESTEEM IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME: A CROSS-SECTIONAL STUDY. - Arya, Simran; Mani, Ankita; Singh, Deeksha; Jain, Shuchi (Student’s Journal of Health Research Africa, 2024)
Background PCOS has serious health issues, affecting female health, causing body disfigurement, lowering self-esteem, decreasing quality of life, and lifelong health consequences related to metabolic disorders. Objective: The objective of the study was to evaluate ‘the impact of various clinical features of PCOS, namely obesity, hirsutism, acne, menstrual irregularities, on psychological well-being in women suffering from PCOS’. Material and methods A cross-sectional study was conducted in the gynecology OPD, Sir Sunderlal Hospital, BHU. Tools used for data collection were a self-structured questionnaire, which included socio-demographic status, menstrual cycle questionnaire, Body Mass Index measurement, waist-hip ratio, and clinical features of PCOS. Hirsutism was assessed by the Ferriman-Gallwey scoring system, the Global acne grading system, self-esteem by the Rosenberg self-esteem scale, and body image by the Body Image Concern Inventory scale. Statistical analysis was done by SPSS version 22. Results Findings of multiple regression analysis suggest that women with hirsutism experienced poorer self-esteem (β= -2.621, p=0.01) and greater body dissatisfaction (β= 0.258, p= 0.02) than women without hirsutism. Furthermore, obese women had a lower level of self-esteem (β= -0.056, p=0.01) and negative body image (β= 0.748, p=0.01) compared with non- obese PCOS women. PCOS women with menstrual irregularities had higher body dissatisfaction (β=0.143, p=0.05) than patients with regular cycles. Conclusion Women suffering from PCOS, having obesity, menstrual irregularities, and features of hyperandrogenism have a profound effect on psychological well-being. So, the recognition of the early signs of PCOS and early treatment can improve the quality of life.